Fundamentals of Entrepreneurship (ENT300) : Huda kitchen / Nurul Huda Ahmad Tajuddin - Ahmad Tajuddin, Nurul Huda (2020)
This special sambal was formulated by my late grandmother. This recipe was original from my grandmother, Saedah Binti Awang Kecil. The recipe was taken from generation to generation. And I am the fourth generation. It’s my pleasure to share this wonderful taste with other. This year will be my third year of running business. The originality taste will attract interest from other. This is because the ingredient was so fresh. We buy the raw material from local people and some of them were planted by me at backyard. Cooking with love and passion also one of the reason this sambal taste incredible. We come out with six types of sambal. Which are sambal kampong (original), sambal petai, spicy jalapeno, sambal hijau, and sambal daging. I really hope the customer enjoy the taste, and have happy meal!!